Butanol production by Clostridium beijerinckii from pineapple waste juice. (October 2018) - Sanguanchaipaiwong, Vorapat; Leksawasdi, Noppol
Abstract: Renewable energy has received increasing attention, due to global energy crisis and limited supply of fossil fuels. Butanol is one of the alternative biofuels with the similar energy properties as gasoline, such as, energy density and heat of vaporization. It could be produced by Clostridia via acetone-butanol-ethanol fermentation from various renewable sources. To obtain economical raw materials, pineapple waste juice was utilized as a carbon source for Clostridium beijerinckii TISTR 1461. The juice was collected from 'Pattavia' pineapple waste and utilized to prepare culture medium. The maximum viable C. beijerinckii concentration (2.40 ± 0.12 x 10 8 CFU/mL) was obtained at 168 h of cultivation with pineapple waste juice under anaerobic condition at 37 °C. The butanol concentration of 3.14 ± 0.16 g/L was subsequently produced. A yield of 0.08 gbutanol ∙g -1 reducing sugars was achieved suggesting the necessity to improve fermentation process for higher level of butanol concentration.